Pharmacogenetic aspects of therapy for autoimmune hepatitis against the background of degenerative-dystrophic joint lesions - Borysenko, Tetiana V.; Babalian, Volodymyr O.; Dorofieieva, Valeriia R.; Danylchenko, Svitlana I.; Fedota, Оlena М. (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. The pathogenesis of autoimmune diseases, including musculoskeletal, gastrointestinal, and endocrine manifestations, involves the interaction of genotype and environmental factors. Pathologies demonstrate comorbidity and clinical heterogeneity even within a single family. Genetic polymorphisms of one-carbon metabolism are key regulators of cellular processes that become therapeutic targets. Description of the case. The study describes personalized therapy for a patient with an autoimmune comorbid disease, with an emphasis on genetic and metabolic characteristics. The treatment regimen is adapted to the features of the one-carbon metabolism profile of a patient with chronic autoimmune hepatitis and degenerative-dystrophic joint disease. Family history includes autoimmune thyroiditis, vitiligo, Parkinson’s disease, cardiovascular diseases. The patient’s genotype for single nucleotide polymorphisms rs1801133, rs1801131, rs1801394, rs1805087, and rs3733890 of the one-carbon metabolism genes is associated with elevated plasma homocysteine levels. After treatment, changes in biochemical parameters were observed: alanine aminotransferase (72→53 U/L), aspartate aminotransferase (53→44 U/L), gamma-glutamyltransferase (129→89 U/L), alkaline phosphatase (313→125 U/L) and homocysteine (15.1→17.0 μmol/L). Conclusion. Positive dynamics after personalized therapy demonstrates the importance of an interdisciplinary approach to etiopathogenetic treatment, emphasizing the need to support hepatobiliary function along with muscular and skeletal therapy.